Pengaruh Konten Media Sosial Edukasi Kesehatan terhadap Perubahan Perilaku Hidup Sehat pada Generasi Z - Palma Juanta; Orville Lim; Ferry, Ferry; Devan Wijaya (Yayasan Literasi Sains Indonesia, 2025)
Social media has become a primary platform for Generation Z to access various types of information, including health education. This study aims to analyze the impact of health education content on social media on behavioral changes towards a healthy lifestyle among Generation Z. The research employs a quantitative approach through a survey involving 53 respondents aged 17-22 years. The findings indicate that health education content on social media effectively raises awareness of the importance of a healthy lifestyle, including balanced nutrition, sufficient physical activity, stress management, and mental health awareness. Additionally, influencers and online communities play a significant role in shaping sustainable healthy habits. However, this study also highlights the challenge of misinformation and hoaxes, which can affect understanding and decision-making regarding health. Therefore, improving media literacy is crucial for Generation Z to differentiate between credible and unreliable information. Furthermore, the involvement of healthcare professionals in producing educational content is essential to ensure accuracy. Thus, social media can be optimized as a more effective, reliable, and impactful health education platform for Generation Z.